INVEST ASI, EKSPOR DAN MASALAH DE-INDUSTRIALISASI DI INDONESIA - Setyawan, Anton Agus; Fatchurrohman, Fatchurrohman (Universitas Muhammdaiyah Surakarta, 2004)
There are two constraints in the process of economic recovery in Indonesia. First, investment rate is decreasing in the last five years. This matter happens due to the bad investment climate in Indonesia. Second, slow growth of export rate in Indonesia. At the present, investment rate in Indonesia is only 22 percent of GDP, while the ideal rate is 30 percent of GDP. Another problem, which may be interrupting the economic recovery, is de-industrialization. The sign of de-industrialization occur by relocation phenomena of FDIfrom Indonesia. This research analyze the effects of direct investment and export to GDP. The tool of analyses of this research is econometric model known as Error CorrecÂtion Models. The results shows that in a long term and short term, export and direct investment do not have a significant effect to GDP. It shows that Indonesia do not have a clear policy about export and investment. The policy implications of this research are government should have a deregulation policy in the industry and recover investment climate.